HDAC1 participates in polycystic ovary syndrome through histone modification by regulating H19/miR-29a-3p/NLRP3-mediated granulosa cell pyroptosis - Chen, Jiying; Zhu, Zhiying; Xu, Shi; Li, Jing; Huang, Lilan; Tan, Wenqing; Zhang, Yonggang; Zhao, Yanli (Molecular and cellular endocrinology, 2023)
Histone deacetylase 1 (HDAC1) is known to participate in the molecular etiology of polycystic ovary syndrome (PCOS). However, its role in granulosa cell (GC) pyroptosis remains unclear. This study sought to investigate the mechanism of HDAC1 in PCOS-induced GC pyroptosis through histone modification. Clinical serum samples and the general data of study subjects were collected. PCOS mouse models were established using dehydroepiandrosterone and cell models were established in HGL5 cells using dihydrotestosterone. Expressions of HDAC1, H19, miR-29a-3p, and NLR family pyrin domain containing 3 (NLRP3) and pyroptosis-related proteins and levels of hormones and inflammatory cytokines were determined. Ovarian damage was observed by hematoxylin-eosin staining. Functional rescue experiments were conducted to verify the role of H19/miR-29a-3p/NLRP3 in GC pyroptosis in PCOS. HDAC1 and miR-29a-3p were downregulated whereas H19 and NLRP3 were upregulated in PCOS. HDAC1 upregulation attenuated ovarian damage and hormone disorders in PCOS mice and suppressed pyroptosis in ovarian tissues and HGL5 cells. HDAC1 inhibited H3K9ac on the H19 promoter and H19 competitively bound to miR-29a-3p to improve NLRP3 expression. Overexpressed H19 or NLRP3 or inhibited miR-29a-3p reversed the inhibition of GC pyroptosis by HDAC1 upregulation. Overall, HDAC1 suppressed GC pyroptosis in PCOS through deacetylation to regulate the H19/miR-29a-3p/NLRP3 axis. •HDAC1 is downregulated in the serum of PCOS patients.•HDAC1 overexpression alleviates the symptoms of PCOS mice and GCs pyroptosis in vitro.•HDAC1 inhibits H3K9ac in the H19 promoter to repress H19 expression.•H19 competitively binds to miR-29a-3p to promote NLRP3 expression.•Overexpressed H19/NLRP3 or inhibited miR-29a-3p facilitates GCs pyroptosis.